Surfactant therapy in pediatric ALI and ARDS: are we there yet? - Facco Marcazzò, M.; Pettenazzo, A. (Acta Biomedica Atenei Parmensis, 2012)
Acute Lung Injury (ALI) and Acute Respiratory Distress Syndrome (ARDS) are serious lifethreatening disorders in the pediatric population, arising from direct or indirect lung damage, leading ultimately to overwhelming lung inflammation and severe hypoxia. In this inflammatory setting, endogenous surfactant is likely to be either lacking or inactivated by plasma proteins, proteases and reactive oxygen species flooding the injured alveoli. Besides supportive treatment (mechanical ventilation with low tidal volumes, positive end-expiratory pressure to open collapsed alveoli, supplemental oxygen, and supportive care of other organs’ failure), exogenous surfactant has been advocates as a possible therapy. However, apart from case reports and small clinical trials, review of the recent literature failed to confirm striking benefit from exogenous replacement therapy. Further studies are needed to confirm a possible role of surfactant in pediatric acute respiratory failure as well as to clarify issues related to this promising therapy.